Analysis of factors related to the incidence of stunting in toddlers based transcultural nursing in the technical implementation unit in the work area of public health center Kaluku Bodoa Makassar - Risnawati, Risnawati; Nurwijayanti, Nurwijayanti; Anggraeni, Novita Anna (Science Midwifery, 2024)
The term "stunting" is used to describe the nutritional condition of a child based on anthropometric standards, based on the PB/U or TB/U index. The aim of the research is to analyze the factors related to the incidence of stunting in toddlers based on transcultural nursing in children aged 24-59 months in the Kaluku Bodoa Makassar Public Health Center TECHNICAL IMPLEMENTATION UNIT working area. The research design used in this study used a quantitative methodology, with a "cross-sectional" approach. Purposive sampling was used to select a sample size of 103 respondents. Data analysis was carried out with research findings showing that the majority of toddlers, specifically 72.8%, were categorized as stunting, as determined through the use of the chi-square test at a significance level of α=0.05, while 27.2% of toddlers were classified as normal from a total of 103 respondents. The research results show that there is a significant relationship between technological factors and the incidence of stunting (p=0.007), social factors and family support (p=0.000), cultural values and lifestyle factors (p=0.000), economic factors (p=0.010), educational factors (p=0.032), and the most influential factors identified were social factors and family support (p=0.000), with a 31 times higher risk of stunting. The P value is 0.000 < 0.005, with a 95% confidence interval (14.828-6.7013).